Peran Kepala Sekolah dalam mencapai sekolah yang unggul - Nofridasari, Erlita Ayu; Hasanah, Enung (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The school principal is the key factor in achieving an excellent school. This research explores the role of the school principal in building an outstanding school. The research method used is a field research method. Data collection is conducted through interviews, and data analysis is performed using qualitative data analysis. The results of the research indicate that the role of the school principal in building an excellent school begins with the establishment of the criteria for an outstanding school, providing continuous guidance and evaluation of teacher performance, as well as providing feedback based on performance evaluations, and implementing proportional rewards and punishments.